STRATEGI PEMBELAJARAN INKUIRI (SPI) DALAM PEMBELAJARAN IPA DI SEKOLAH DASAR - MARINI, YESI (Universitas Negeri Padang, 2014)
Abstrac This rescarch was conducted to describe the improvement of the students” learning achievement in natural science by using inquiry learning strategy.This was classroom Action Research which applied either qulitive or quantitative approaches. The subject of the research was the teacher and the students in grade V . The data of the research were in the form of information related to resultof observation on the plan. Theimprovement of the students” learning achievement in natural science by using inquiry learning strategy.This was classroom Action Research which applied either qulitive or quantitative approaches 71,41 % in cycle I to 82,05 % in cycle II and most of them got very good scores.